The Epidemiology and Outcomes of Women With Postpartum Hemorrhage Requiring Massive Transfusion With 8 or More Units of Red Cells: A National Cross-sectional Study. Issue 4 (December 2017) - Green, L.; Knight, M.; Seeney, F.M.; Hopkinson, C.; Collins, P.W.; Collis, R.E.; Simpson, N.A.B.; Weeks, A.; Stanworth, S.S.
Abstract : ( BJOG . 2016;123:2164–2170) The frequency of postpartum hemorrhage (PPH) and the rates of severe adverse outcomes associated with PPH have increased in developed countries over the last 10 to 15 years. PPH also remains a leading cause of maternal morbidity and mortality worldwide. The multifactorial approach to treating PPH consists of early identification and supportive resuscitation, along with pharmacological, mechanical and surgical methods to control bleeding. A population-based cross-sectional study was undertaken using the United Kingdom Obstetric Surveillance System to determine the incidence of massive transfusion (MT) in obstetrics in the UK and to determine the management practices used and the outcomes for parturients receiving MT.